2008
DOI: 10.7326/0003-4819-149-2-200807150-00007
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis: Combination Endoscopic and Drug Therapy to Prevent Variceal Rebleeding in Cirrhosis

Abstract: A combination of endoscopic and drug therapy reduces overall and variceal rebleeding in cirrhosis more than either therapy alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
76
0
5

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(86 citation statements)
references
References 36 publications
5
76
0
5
Order By: Relevance
“…The authors have demonstrated a significant impact on mortality with the use of terlipressin, when compared to placebo (79) . Even though the use of vasoactive drugs has been shown to be comparable to endoscopic treatment in the control of bleeding (45) , there are data showing that combined treatment with vasoactive drugs and endoscopic hemostasis is superior to each treatment modality in the control of bleeding and prevention of bleeding recurrence (7,9,72,94,155) . Of note, impact in reduction of mortality was observed in only one RCT that evaluated combination treatment of variceal bleeding with terlipressin and endoscopic therapy (94) .…”
Section: Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors have demonstrated a significant impact on mortality with the use of terlipressin, when compared to placebo (79) . Even though the use of vasoactive drugs has been shown to be comparable to endoscopic treatment in the control of bleeding (45) , there are data showing that combined treatment with vasoactive drugs and endoscopic hemostasis is superior to each treatment modality in the control of bleeding and prevention of bleeding recurrence (7,9,72,94,155) . Of note, impact in reduction of mortality was observed in only one RCT that evaluated combination treatment of variceal bleeding with terlipressin and endoscopic therapy (94) .…”
Section: Recommendationsmentioning
confidence: 99%
“…Even in the absence of active bleeding, endoscopic treatment of esophageal varices is recommended after exclusion of other possible bleeding lesions, since a third of these patients with variceal hemorrhage have no signs of active bleeding at the moment of endoscopy (91) . Combined endoscopic and pharmacologic treatment is superior to each treatment modality (7,9,72,94,156) , but the use of vasoactive drugs should precede endoscopic hemostasis. Esophageal band ligation is the endoscopic treatment of choice (132) .…”
Section: ) Endoscopic Treatment Of Acute Variceal Bleedingmentioning
confidence: 99%
“…The effect of carvedilol is similar to the propranolol or nadolol associated to prazosin and more potent (16%-43% vs pre-treatment values) compared to isolated propranolol or nadolol (12%-13% vs pretreatment values) (BANARES; MOITINHO et al, 2002). Carvedilol achieves a good hemodynamic response in more than 50% of patients non-responder to propranolol (REIBERGER; ULBRICH et al, 2013;GONZALEZ;ZAMORA et al, 2008;GARCIA-TSAO;.…”
Section: Artigos De Revisãomentioning
confidence: 98%
“…Conducted clinical trials comparing only non-selective beta blockers, non-selective beta blockers with mononitrates and endoscopic band ligation of varices demonstrated comparable efficacy in the prevention of recurrent bleeding and survival (17). The most recent meta-analysis suggests that combined therapy: pharmacotherapy and endoscopic therapy, is the most effective method (18).…”
Section: Prophylaxis Of Recurrent Bleeding Varicesmentioning
confidence: 99%